CD226: An Emerging Role in Immunologic Diseases - Huang, Zhiyi; Qi, Guangyin; Miller, Joseph S.; Zheng, Song Guo (Frontiers in Cell and Developmental Biology, 2020)
CD226, a member of the immunoglobulin superfamily, is a functional protein initially expressed on natural killer and T cells. In recent years, the function of CD226 has been increasingly realized and researched. Accumulating evidence shows that CD226 is closely related to the occurrence of autoimmune diseases, infectious diseases, and tumors. Because of the CD226’s increasing importance, the authors herein discuss the structure, mechanism of action, and role of CD226 in various pathophysiological environments, allowing for further understanding of the function of CD226 and providing the basis for further research in relative diseases.